2005
DOI: 10.1097/01.mao.0000178119.46290.e1
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Iatrogenic Temporal Lobe Encephalocele after Canal Wall Down Mastoidectomy in the Presence of Active Cholesteatoma

Abstract: A temporal lobe encephalocele can be safely repaired while maintaining a mastoid bowl. This may be the safest treatment option for patients with active cholesteatoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 8 publications
0
22
0
1
Order By: Relevance
“…While many agree that chronic otitis media, cholesteatoma, and iatrogenic injury can be potential causes of temporal bone encephaloceles [2,4,6,8], there has been disagreement with regard to the etiology of spontaneous or idiopathic temporal bone encephaloceles [1,7,9,10].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…While many agree that chronic otitis media, cholesteatoma, and iatrogenic injury can be potential causes of temporal bone encephaloceles [2,4,6,8], there has been disagreement with regard to the etiology of spontaneous or idiopathic temporal bone encephaloceles [1,7,9,10].…”
Section: Introductionmentioning
confidence: 98%
“…Previous authors have classified encephaloceles according to their anatomic site of origin [3]. Others have classified them further based on their etiology and management [1,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…McMurphy and Oghalai (13) reported that CT alone can be misleading in postoperative states. They considered MRI essential for differentiation between granulation tissue, cholesteatoma and brain herniation.…”
Section: Discussionmentioning
confidence: 98%
“…Although it mostly depends on congenital skull base defects, trauma, infection, and tumours, idiopathic and iatrogenic cases are also encountered [14]. They are usually observed in patients who underwent mastoid cavity surgery due to chronic otitis media with or without cholesteatoma [5, 6]. The incidence of encephalocele developed due to tegmen defect is decreased with the use of broad-spectrum antibiotics and technological developments in ear surgeries [5].…”
Section: Introductionmentioning
confidence: 99%
“…They are usually observed in patients who underwent mastoid cavity surgery due to chronic otitis media with or without cholesteatoma [5, 6]. The incidence of encephalocele developed due to tegmen defect is decreased with the use of broad-spectrum antibiotics and technological developments in ear surgeries [5]. Although there is no standard surgery protocol, three approaches are generally acceptable: middle fossa approach, transmastoid approach, and combination of both [3, 5].…”
Section: Introductionmentioning
confidence: 99%